2006
DOI: 10.1097/01.ijg.0000212236.96039.9c
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cell Proliferation by Mitomycin C Incorporated into P(HEMA) Hydrogels

Abstract: This study demonstrates that a slow release form of MMC can inhibit cell proliferation in vitro. Future experiments will focus upon the efficacy of this polymer-bound form during in vivo wound healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…In the GH-MMC group, the exposed concentration for the initial 3 days was 2 lg MMC in 0.0375 mL (0.0375 g) solution, 0.054 mg/g MMC per day, which was higher than 0.04 mg/g, the minimum concentration needed for inhibiting conjunctival fibroblast proliferation in vitro. 24 Taken together, the amount of MMC released from the GH in the present study should be effective for suppressing scar formation after glaucoma surgery and should induce less toxicity to the conjunctiva.…”
Section: Discussionmentioning
confidence: 61%
“…In the GH-MMC group, the exposed concentration for the initial 3 days was 2 lg MMC in 0.0375 mL (0.0375 g) solution, 0.054 mg/g MMC per day, which was higher than 0.04 mg/g, the minimum concentration needed for inhibiting conjunctival fibroblast proliferation in vitro. 24 Taken together, the amount of MMC released from the GH in the present study should be effective for suppressing scar formation after glaucoma surgery and should induce less toxicity to the conjunctiva.…”
Section: Discussionmentioning
confidence: 61%
“…4,5 In 2002, we initiated studies to incorporate the antifibrotic drug mitomycin C into a poly(2-hydroxyethyl methacrylate) (P[HEMA])-based drug-release device. 6 The P(HEMA) polymer was washed to remove low-molecular-weight toxicants that remained after polymerization, and the mitomycin C was subsequently loaded into the matrix using a novel mechanism. This polymer enabled release of the drug on contact with water.…”
mentioning
confidence: 99%
“…The results demonstrated that the P(HEMA) polymer enabled release of mitomycin C and inhibited the proliferation of fibroblasts in a dose-dependent manner. 6 The objectives of the present study were (1) to develop techniques for preparation and standardization of P(HEMA) disks loaded with mitomycin C; (2) to demonstrate that the device released mitomycin C both in vitro and in vivo when attached to a commercially available flexiplate silicone Ahmed glaucoma valve (AGV) (model FP7; New World Medical, Inc, Rancho Cucamonga, California); and 3to determine the effects of the modified device after implantation in a rabbit model.…”
mentioning
confidence: 99%
“…In a recent example, it was shown that long-term mitomycin C release could be measured up to 3 months postoperatively but was associated with retinal impairment in rabbit models in vivo [25,46]. Hydrogels and non-degradable polymers as well as biodegradable polymers have been used as antifibrotic drug delivery systems in animal studies [25,47,48]. …”
Section: Discussionmentioning
confidence: 99%